Comunidade de morcegos (Mammalia) em fragmento de Mata Atlântica de Sergipe : estrutura da comunidade e atividade temporal - Brito, Daniela de Vasconcelos (2014)
The fragmentation of the landscape provides, among others, the occurrence of edge habitats, implying different responses of bats in this condition. We aimed in this study to analyze the community structure of bats in edge and interior of forest environments and to characterize the activity of frugivorous species in an Atlantic Forest fragment of Sergipe, northeastern Brazil. The study was done at Refúgio de Vida Silvestre Mata do Junco (RVSMJ), municipality of Capela. The sampling occurred between November 2012 and October 2013, with monthly samples in the edge and inside the forest in two areas for three consecutive nights in each area between 1800 to 2400 p.m., using ten mist nets. With a sampling effort of 116,640 h.m² we captured 96 bats belonging to 12 species, of which Lophostoma brasiliense and Micronycteris schmidtorum represent new records to the RVSMJ and Atlantic Forest area in Sergipe. The parameters of richness, abundance and diversity did not show differences between the edge and interior. However the species composition differed between these environments and the bats had different edge-sensitivity, indicating that bats are affected by the formation of edge in the locality. Regarding the activity, the species were already active in the first hour of sampling and remained in continuous activity during the sample period. There was a high temporal overlap in activity between A. lituratus and D. cinerea (Øjk = 0,813) and between C. perspicillata and D. cinerea (Øjk = 0,734). The temporal activity pattern of the bat community at the RVSMJ showed relatively common characteristics to the activity of fruit bats, but the absence of differences between schedules and between species activities can be a reflex of the small sample size.